Knowledge Economics: Theory and Practice - Bahronkul Mamatkulovich, Babakulov; Alisher Batirovich, Mirzaxodjaev; Akmal Merojovich, Amirov (International Journal of Psychosocial Rehabilitation, 2020)
In this article, the author, analyzing the theoretical aspects of the formation and development of the knowledge economy, suggested his point of view on this issue